Mapping Scholarship on Generation Z in Participatory Communication for Sustainable Development (2015–2025): A Bibliometric Analysis - Aminah Swarnawati; Robby Milana (Jurnal Riset Komunikasi, 2026)
This study maps scholarly literature on Generation Z in participatory communication for sustainable development published between 2015 and 2025. Using bibliometric analysis, the article examines publication growth, geographical distribution, authorship networks, citation patterns, and keyword co occurrence to identify how this field of research has developed over time. The analysis shows a significant increase in publications after 2020, with Indonesia emerging as a major contributor in terms of output, while citation influence remains concentrated in the Global North. Co authorship patterns indicate limited cross regional collaboration, suggesting persistent structural asymmetries in knowledge production. Keyword mapping reveals three dominant thematic orientations, namely community participation, digital engagement, and sustainability related challenges. Rather than assessing participatory practices or youth engagement empirically, this study focuses on how Generation Z and participatory communication are constructed within academic scholarship. By providing a systematic overview of research trends and structural patterns, the article contributes to a clearer understanding of the organization and limitations of current knowledge in this field.